ChemInform Abstract: Difluorohomologation of Ketones. Issue 26 (June 2015) - Kosobokov, Mikhail D.; Levin, Vitalij V.; Struchkova, Marina I.; Dilman, Alexander D.
Abstract The one‐pot three‐step sequence for the difluorohomologation of ketones involves silylation, difluorocyclopropanation of silyl enol ethers followed by highly regioselective ring opening of cyclopropane intermediates.